Joyful Literacy Learning/Teaching Within a University-Based Summer Literacy Camp - Scheffel, Tara-Lynn; Correia, Bethany (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
This case study explores the thematic thread of joy within the patterned quilt (Dyson & Genishi, 2005) of a longitudinal university-based summer literacy camp (for ages 4 to 12) led by pre-service teachers. We explore pre-service teachers’ roles as curriculum makers in relation to examples of negotiated curriculum leading to shared joyful literacy learning.